2002
DOI: 10.2320/matertrans.43.1069
|View full text |Cite
|
Sign up to set email alerts
|

Activated Carbon Sphere with Antibacterial Characteristics

Abstract: The activated carbon sphere containing zinc oxide was prepared by carbonizing a zinc ion-exchange resin at different temperatures in nitrogen gas. Zinc oxide of hexagonal type was detected in all carbon samples, the amount of which decreased with an increase in the carbonization temperature. However, the specific surface areas of carbon samples increased with increasing temperature of the resin. The antibacterial activity on their carbon samples was studied without the presence of light. The antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In this regard, metal-oxide nanoparticles like magnesium oxide and zinc oxide have attracted much attention in recent years due to their greater stability under harsh conditions and good antimicrobial activity even in the absence of light [5,6]. Moreover, these particles contain minerals that are essential to human health and hence exhibit higher toxicity toward human pathogens [7].…”
Section: Introductionmentioning
confidence: 98%
“…In this regard, metal-oxide nanoparticles like magnesium oxide and zinc oxide have attracted much attention in recent years due to their greater stability under harsh conditions and good antimicrobial activity even in the absence of light [5,6]. Moreover, these particles contain minerals that are essential to human health and hence exhibit higher toxicity toward human pathogens [7].…”
Section: Introductionmentioning
confidence: 98%
“…5), 10) On carbon samples, however, the pH values do not aect the antifungal activity, because of the pH of about 5.7. Yamamoto et al 7) have found the generation of H 2 O 2 from the surface of ZnO in carbon samples and claried that the generated H 2 O 2 was eective for growth inhibition of bac teria. Therefore, the occurrence of antifungal activity in present work is anticipated with the generation of H 2 O 2 , as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on the effect of ZrO 2 additions by different investigators [45][46][47][48][49][50][51][52] (Fig. 7) that the densification was promoted by inhibition of growth of CaO grains at a higher temperature (e.g.…”
Section: Zirconiamentioning
confidence: 99%
“…The effects of Al 2 O 3 additive on the properties (apparent porosity, grain growth) and hydration resistance of CaO and CaOcontaining materials have been extensively investigated in relation to sintering temperature and holding time. 8,48,52,69,[73][74][75][76][77][78] Addition of Al 2 O 3 along with SiO 2 and MgO (added or present as impurities) greatly decreases the temperature of liquid formation in the CaO matrix, from 1370uC in the CaO-Al 2 O 3 binary phase diagram to about 1100-1150uC. 77 The dihedral angle between liquid formed by CaO containing a small amount of Al 2 O 3 and CaO refractory is reported to be ,10u.…”
Section: Alumina and Al Metalmentioning
confidence: 99%
See 1 more Smart Citation